Effect of aminophylline on fatigue of the sternomastoid muscle in man. Issue 2 (February 1986) - Efthimiou, J; Fleming, J; Edwards, R H; Spiro, S G
Abstract : The effect of intravenous aminophylline on the contractility of the sternomastoid muscle was measured in the fresh state and after the induction of significant fatigue in five normal subjects. Fatigue was produced by repetitive isometric neck flexion, for two seconds every four seconds at 70% of the maximum voluntary contractile force, continued until exhaustion. Each subject performed three experiments, one to two weeks apart, in random order. In experiment 1 fatiguing exercise and recovery were completed without aminophylline; in experiment 2 intravenous aminophylline was started 30 minutes before exercise and continued throughout the 60 minute recovery period; and in experiment 3 intravenous aminophylline was started immediately after the end of exercise. Aminophylline did not influence the frequency-force relationships, relaxation rate, or maximum voluntary contractile force in the fresh muscle. After fatiguing exercise there was a relatively selective reduction in force response to stimulation frequencies of less than 30 Hz, with little alteration in forces at higher frequencies–that is, low frequency fatigue–and this effect was present for the entire one hour study period. Aminophylline given before or immediately after fatigue did not influence the recovery of either low frequency fatigue or maximum voluntary contractile force. Aminophylline at therapeutic concentrations had no significant effect on the contractility or fatiguability of the normal human sternomastoid muscle.